Statistical Study of F‐Region Short Period Ionospheric Disturbances Related to Convection in the Lower Atmosphere Over Wuhan, China - Zhenlin Yang; Sheng‐Yang Gu; Yusong Qin; Chen‐Ke‐Min Teng; Fuqing Huang; Wenjie Sun; Xiankang Dou (Space Weather)
Abstract We investigated the relationship between convective activity and F‐region short‐period ionospheric disturbances at middle latitudes from 2018 to 2020. The ionospheric variations were extracted from the total electron content (TEC) data obtained by the BeiDou geostationary orbit receiver in Wuhan, China, while the convective activities were represented by precipitation data from the fifth generation European Center for Medium‐Range Weather Forecasts Reanalysis (ERA5). Additionally, an ionosonde located in Wuhan, China, was used to study the variation in the sporadic E (Es)‐layer. Seasonal variations in the convective activity and TEC disturbances were studied. It was found that short‐period ionospheric disturbances occurred mainly around summer midnight and around the June solstice. In addition, the correlations between convective activity and the ionosphere have also been studied. A positive correlation between precipitation and short‐period ionospheric disturbances was found. Similarly, precipitation and foEs also had a positive correlation. By analyzing the precipitation azimuth and upward propagation of convective gravity waves, we proposed a possible coupling mechanism between the ionosphere and the troposphere, through which convective gravity waves could indirectly affect F‐region short‐period ionospheric disturbances by modulating the Es‐layer.